Capillimicrobium parvum gen. nov., sp. nov., a novel representative of Capillimicrobiaceae fam. nov. within the order Solirubrobacterales, isolated from a grassland soil. Issue 8 (26th August 2022) - Vieira, Selma; Huber, Katharina J.; Geppert, Alicia; Wolf, Jacqueline; Neumann-Schaal, Meina; Luckner, Manja; Wanner, Gerhard; Müsken, Mathias; Overmann, Jörg
Abstract : The order Solirubrobacterales is a deep-branching lineage within the phylum Actinomycetota . Most representatives have been isolated from terrestrial environments. A strain isolated from a grassland soil was found to be affiliated with this order and therefore characterized by a polyphasic approach. Cells of strain 0166_1 T are Gram-positive, short rods, non-motile, non-spore-forming and divide by binary fission. A surface layer with protrusions covers the majority of the cells. Strain 0166_1 T grows optimally around neutral to slightly alkaline pH (pH 7.1–7.9) and at temperatures between 24–36 °C in SSE/HD 1 : 10 medium. It grows optimally with 0–0.5% NaCl (w/v) but can withstand concentrations up to 5 %. The major fatty acids are C18 : 1  ω9 c, C16 : 1  ω 7 c, C17 : 0 cyclo ω 7 c, C18 : 1  ω7 c methyl and C19 : 0 cyclo ω 9 c . The major polar lipids are diphosphatidylglycerol, two unidentified phospholipids and one unidentified glycolipid. MK-7(H4) and MK-7(H2) are the predominant respiratory quinones. meso -2, 6-Diaminopimelic acid is the diagnostic diamino acid in the cell-wall peptidoglycan. The G+C content for strain 0166_1 T is 72.8 mol%. 16S rRNA gene sequence analysis indicated that this bacterium was related to Conexibacter arvalis KV-962 T and Conexibacter stalactiti YC2-25 T with 95.5 and 95.2 % sequence similarity, respectively. Based on the phenotypic, genomic and phylogenetic data, we propose the novel species Capillimicrobium parvum sp. nov. (type strain 0166_1 T =DSM 104329 T =LMG 29999 T =CECT 9240 T ) of the novel genus Capillimicrobium gen. nov. within the novel family Capillimicrobiaceae fam. nov.